Hubungan Antara Tinggi Badan Dan Power Otot Tungkai Dengan Hasil Lari Jarak Pendek Di MIN 04 Kepahiang : The Relationship Between Leg Muscle Power And Height With The Results Of Short Distance Running At MIN 04 Kepahiang - Muhammad Noer Kholis; Syafrial; Arwin (Universitas Bengkulu, 2023)
Abstract The problem in this study is whether there is a relationship between leg muscle power and height on the results of short distance running. While the aim is to find out whether there is a relationship between leg muscle power and height on the results of short distance running. This type of research is descriptive research. The sample of this research is the students of class V MIN 04 Kepahiang, totaling 40 people. Based on the data normality test, for X1 obtained Lcount = 0.0951 < Ltable = 0.13885, for X2 obtained Lcount = 0.1304 < Ltable = 0.13885, and for Y obtained Lcount = 0.1357 < Ltable = 0.13885 , so it can be concluded that all data are normally distributed. Based on the data correlation test, it can be concluded that the greater the leg muscle power, the faster the short distance running results, the taller the body, the faster the short distance running results, and the higher the body the greater the leg muscle power produced. Furthermore, based on the multiple correlation test, obtained rcount = 0.501647 > rtable = 0.312 so it can be concluded that there is a significant relationship between leg muscle power and height with short distance running results with a moderate correlation with a determination of 25.165%. Keyword : leg muscle power, height, and short distance running results